The introduction of the didactical tool PSeInt in the teaching and learning process: a proposal for Linear Algebra - Beúnes Cañete, Ing. José Enrique; Vargas Ricardo, M. Sc. Anelys (Transformación, 2024)
Objective: Informatics tools offer university professors new resources to change traditional teaching. This paper gives arguments to introduce PSeInt, a software widely used in Latin America, in the teaching and learning process of Lineal Algebra. Methods: Theoretical methods were used to construct a framework for the proposal. Likewise, the foundations, structure, functioning and possibilities of PSeInt software was analyzed to consider the software as a material of the research. Results: The main finding of the research is the statement of theoretical premises for using PSeInt software in the teaching and learning process of Linear Algebra, together with an illustration of suitable tasks. Conclusions: The introduction of this tool favors the development of algorithmically thinking, the comprehension of conceptual relations, an interdisciplinary approach and students’ motivation.